PROFIL SEL EPITEL DAN LEUKOSIT MUKOSA VAGINA SAPI PASUNDAN DARA SELAMA SIKLUS ESTRUS - Bayani, Matni Syifa; Hilmia, Nena; Ramdani, Diky; Hidayat, Rahmat; Daud, Andre Rivianda; Hernaman, Iman; Widyastuti, Rini (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
The estrous cycle is the period between two consecutive estrus phases regulated by reproductive hormones. A method used for determining the estrous cycle in cattle involves investigating the epithelial cells and leukocytes found in the vaginal mucosa by using vaginal smear techniques. This study aims to identify the epithelial cells and leukocytes that dominate each phase of the estrous cycle in Pasundan heifers, along with the duration of each phase. The study was conducted at the Teaching Farm Ciparanje and the Animal Reproduction Laboratory, Faculty of Animal Husbandry, Universitas Padjadjaran. The study included a sample of 17 Pasundan heifers as experimental animals. The research method applied is descriptive quantitative. The assessed parameters included the number of vaginal epithelial cells (parabasal, intermediate, and superficial), the percentage of leukocytes, and the duration of each phase of the estrous cycle. Observations were carried out for three months. The findings revealed that intermediate cells dominated the epithelial cells during the proestrus phase, superficial cells during the estrus phase, and parabasal cells during the metestrus and diestrus phases. While, the lowest leukocyte count was discovered during the estrus phase, and the greatest during the diestrus phase. Furthermore, the proestrus phase in Pasundan heifers lasted for a period of 2-4 days, the estrus phase lasted for 1-2 days, the metestrus phase lasted for 3-5 days, and the diestrus phase lasted for 11-13 days. The estrous cycle of Pasundan heifers typically lasts between 17 and 25 days.